Experimental Robust Optimal Machining of Hardened AISI 420 Stainless Steel With Al2O3+TiCN Mixed Ceramic Tool - Acar, Erdem; Camuşcu, N.; Er, Ali Osman; Aslan, Ednan (My University, 2011)
The high hardness and wear resistance levels of Alumina (Al 2O3)-based ceramics make them excellent choices for incorporation into cutting tools that can be used to machine hardened steels. However, their poor fracture behaviour usually leads to catastrophic failures when they are used in these machining tasks. Thus, there is a need for an investigation that probes the effect of cutting parameters on the machining of hardened steels with Al2O3-based ceramic cutting tools and isolates a set of optimal values of cutting parameters. This paper is such a study. An experimental study that is guided by Taguchi's techniques is performed to analyse the effects of three cutting parameters: cutting speed; feed rate; and depth of cut on two performance measures, flank wear and surface roughness. The robust optimal cutting parameters for each performance measure are reported.
Keywords: Analysis of variance; Experimental design; Hardened steels; Metal cutting; Robust optimization; Taguchi techniques